Strategi Guru dalam Memotivasi Minat Belajar Siswa di Kelas IV SD Negeri Lambaro Angan Aceh Besar - Mutiara Ara Ini; Bukhari Bukhari; Aida Fitri (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This research was conducted to describe the strategies needed by teachers to motivate students' interest in learning and to identify what obstacles were faced by teachers when motivating students' interest in learning in grade IV SD Negeri Lambaro Angan Aceh Besar. The approach used in this study is a qualitative approach using descriptive research. The research location is at SD Negeri Lambaro Angan Aceh Besar, which takes the subject of two teachers, namely grade IV teachers A-B. Researchers used two data collection techniques, namely observation and interviews, and analyzed using data reduction, data presentation, and conclusion drawing/verification. According to the results of data analysis carried out by researchers to motivate students' interest in learning, teachers have their own indicators in motivating students' learning interests. The strategies used by teacher IVA are the use of initial conditioning, learning comfort, a combination of learning methods, creative learning, and positive praise. Meanwhile, teacher IVB has strategies, namely, different learning, a conducive classroom atmosphere, creating questions and questions that will be answered again, effective media, and verbal appreciation. While the obstacles experienced by teachers when motivating students' interest in learning are the lack of awareness and concentration of students while undergoing learning activities so that students do not understand the material taught by the teacher.